Полиакриламид - Абрамова Л. И. Людмила Ивановна; Байбурдов Т. А. Тельман Андреевич; Григорян Э. П. Эльвира Петровна; Зильберман Е. Н. Ехиэл Наумович; Куренков В. Ф. Валерий Федорович (Москва, Химия, 1992)
Авт. указаны на обороте тит. л.